Assessment of rockfall susceptibility along the expressway based on the CF-AHP coupling model: A case study of the Tucheng-Wanglong section of the Rongzun expressway - Jianguo CHEN; Lianxiang ZHONG (Zhongguo dizhi zaihai yu fangzhi xuebao, 2023)
Frequent geological hazards have occurred along the Rongzun Expressway (Tucheng - Wanglong section, posing a threat to the safety of the highway and even human life and property. This study investigated the causes of rockfall along the expressway and identified nine influencing factors, including terrain fluctuation, elevation, normalized difference vegetation index (NDVI), slope direction, lithology, distance from the road, distance from the river, slope, and rainfall. The certainty factor model (CF), analytic hierarchy process (AHP), and coupling model (CF-AHP) were used to evaluate the susceptibility of geological hazard in the study area, and the accuracy of the three models was tested using the distribution of rockfalls at various levels and the success rate curve. The results indicated that the AUC evaluation accuracy of CF, AHP and CF-AHP was 0.848, 0.835 and 0.866, respectively. The frequency ratios of high and moderate prone areas of geohazards obtained by the three evaluation models accounted for more than 70% of the total frequency ratios. The accuracy of the three models in descending order is CF-AHP, CF, AHP models, respectively. This indicates that the CF-AHP model is better than the single CF and AHP models in geohazard prediction and can accurately evaluate the geohazard susceptibility of expressway. It provides a decision-making basis for disaster prevention and mitigation of regional rockfall disaster along the highway.